Objektivní diagnostika lékových alergií se zaměřením na beta-laktamová antibiotika - Panzner, Petr; Krauz, Vladimír; Hanzlíková, Jana; Haschová, Markéta (Iga MZ ČR, 2000)
We would like to contribute to the specification of the relative frequency of drug allergy, especially the clinically most important immediate allergy, in comparison to the frequency of other adverse effects. This will be done by means of the symptom history analysis and by means of the laboratory and skin tests for allergy diagnosis.
Závěrečná zpráva o řešení grantu Interní grantové agentury MZ ČR
Keywords: ELISA; Enzyme-Linked Immunosorbent Assay; ANTIBIOTIKA LAKTAMOVÁ; Immunoglobulin E; Skin Tests; imunoglobulin E; alergologie a imunologie; Medical History Taking; anamnéza; kožní testy; léková alergie; Drug Hypersensitivity